Hechtia glomerata Zucc: Phytochemistry and Activity of Its Extracts and Major Constituents Against Resistant Bacteria - Tommaso Stefani; Elvira Garza-González; Verónica M. Rivas-Galindo; María Yolanda Rios; Laura Alvarez; María del Rayo Camacho-Corona (Molecules, 2019)
Hechtia glomerata Zucc. is used both as a source of food and in ethnomedicine to treat various diseases derived from bacterial infections such as bronchitis, laryngitis, nephritis, whooping cough, urethritis, and sepsis. There are no previous reports about its chemistry and biological activities. Therefore, the aims of this study were to identify components from organic and aqueous extracts of H. glomerata and test the extracts and major isolate compounds against resistant bacteria. Hexane, CHCl3/MeOH, and aqueous extracts were prepared and analyzed by different chromatographic techniques. Structural elucidation was carried out by NMR spectroscopy and X-ray diffraction. The antibacterial activities of extracts, phytochemicals, and semisynthetic derivatives against resistant bacteria were determined by the broth micro-dilution method. From the hexane extract nonacosane (1), hexatriacontanyl stearate (2), hexacosanol (3), oleic acid (4), and β-sitosterol (5) were isolated and characterized. From the CHCl3/MeOH extract, p-coumaric acid (6), margaric acid (7), caffeic acid (8), daucosterol (9), and potassium chloride (10) were isolated and characterized. A total of 58 volatile compounds were identified by GC-MS from the hexane extract and two solids were isolated from the CHCl3/MeOH extract. The UPLC-QTOF-MS analysis of the aqueous extract allowed the identification of 55 polar compounds. Hexane and aqueous extracts showed antibacterial activity against ESBL Escherichia coli, and three strains of Klebsiella pneumoniae ESBL, NDM-1 +, and OXA-48 with MIC values of 500 µg/mL. The CHCl3/MeOH extract was devoid of activity. The activity of phytocompounds and their semisynthetic derivatives toward resistant bacteria was weak. The most active compound was β-sitosterol acetate, with a MIC value of 100 µg/mL against carbapenem-resistant A. baumannii. This is the first report of the secondary metabolites of H. glomerata Zucc. and the activity of its extracts and major pure compounds against resistant bacterial strains.